2019
DOI: 10.1002/jcla.23040
|View full text |Cite
|
Sign up to set email alerts
|

Association ofGCKgene DNA methylation with the risk of clopidogrel resistance in acute coronary syndrome patients

Abstract: Backgrounds Clopidogrel resistance (CR), which was manifested as the failure of platelet inhibition in clopidogrel treatment, was likely to lead to cardiovascular events. Our study was aimed to explore the contribution of DNA methylation in glucokinase (GCK) to the CR risk. Methods Among 36 CR and 36 non‐CR acute coronary syndrome (ACS) patients, the platelet functions were evaluated by VerifyNow P2Y12 assay (turbidimetric‐based optical detection) and DNA methylation levels on two fragments of the CGI from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…DNA methylation might be another novel molecular marker for the identification of higher platelet reactivity. Previous studies indicate that methylation levels of the P2Y12 , 38 PON1 39 and GCK 17 promoter might be related to a decline in clopidogrel response. One study also pointed out that P2Y12 promoter hypomethylation correlates with higher platelet activity and a poor risk of ischaemic events 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation might be another novel molecular marker for the identification of higher platelet reactivity. Previous studies indicate that methylation levels of the P2Y12 , 38 PON1 39 and GCK 17 promoter might be related to a decline in clopidogrel response. One study also pointed out that P2Y12 promoter hypomethylation correlates with higher platelet activity and a poor risk of ischaemic events 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The participants of this study were selected from this cohort, and they provided informed written consent. According to our previous research, 17 the patients who fulfilled the criteria were enrolled in our database. The inclusion criteria were as follows: (1) according to the recent ACC/AHA guidelines, ACS patients who underwent PCI using drug‐eluting stents, with most having multi‐vessel disease of the coronary arteries or left main vessel disease; (2) patients who were administered 300‐mg aspirin and 300‐mg clopidogrel as a loading dose before PCI and received 100‐mg aspirin and 75‐mg clopidogrel daily as a maintenance dose; (3) all the patients were administered pantoprazole to protect the gastrointestinal bleeding; patients were older than 18 years, and (4) without aspirin resistance (ARU less than 550).…”
Section: Methodsmentioning
confidence: 99%
“…Usually, the DNA hypermethylation [25], and another study indicated that P2Y12 promoter hypomethylation was correlate to higher platelet-activity and a poor risk for ischaemic events [26]. Former studies also indicated that methylation levels of P2Y12 [27], PON1 [28], and GCK [29] promoter might be relative to a decline in clopidogrel responding. Additionally, clinical pharmacokinetics research revealed that hypomethylation of the PON1 promoter may be a risk factor for bleeding after dual antiplatelet therapy [30].…”
Section: Discussionmentioning
confidence: 99%
“…GCK (located at 7p15.3-p15.1) encodes a glucose enzyme and catalyses the committed step of insulin secretion, balances glucose homeostasis and regulates glycogen synthesis [7]. Our former study revealed that the higher methylation of cg18492943 would lower the GCK mRNA expression, leading to high platelet activity in non-DM patients [8].…”
Section: Introductionmentioning
confidence: 90%
“…A recent report demonstrated that lower platelet count was associated with larger mean platelet volume, which reflected greater prothrombotic activity [ 32 ]. Another report demonstrated an association between total cholesterol level and clopidogrel resistance [ 33 ]. However, these associations remain controversial and the mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%